Clinical profile of patients presented with esophageal carcinoma in tertiary care teaching medical college of Gujarat, India - Kumar, Santosh; Shah, Amit; Pandya, Hetal; Shah, Meera (International Journal of Advances in Medicine, 2019)
Background: Esophageal cancer is associated with multiple risk factors and associated with poor prognosis. Incidence of Esophageal cancer is increases now a days and it became a sixth leading cause of cancer related death in world. The purpose of this study was to know the clinical profile of patients of esophageal cancer in a tertiary care teaching hospital of Gujrat, India. Methods: This is a retrospective hospital record based study for a period of 2015 to 2018 in which 103 patients with endoscopic biopsy confirmed cases of esophageal cancer were analyzed for clinical profile. Results: Esophageal cancer was most common in low socioeconomic men (66%) of 5th decades (26.21%) associated with tobacco chewing (64.07%) as a major risk factor and dysphagia (86.76%) as most common presenting feature. Most common type and involvement were sqamous type (72.81%) and distal third (50.48%) part of the esophagus respectively. Conclusions: Primordial prevention and screening of patients may decrease mortality related to esophageal carcinoma.